2011
DOI: 10.1590/s0004-28032011000100006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prolonged 48-h wireless capsule esophageal pH monitoring on diagnosis of gastroesophageal reflux disease and evaluation of the relationship between symptoms and reflux episodes

Abstract: -Context -Gastroesophageal reflux disease is one of the most common digestive diseases and an important cause of distress to patients. Diagnosis of this condition can require ambulatory pH monitoring. Objectives -To determine the diagnostic yield of a wireless ambulatory pH monitoring system of 48-hours, recording to diagnose daily variability of abnormal esophageal acid exposure and its symptom association. Methods -A total of 100 consecutive patients with persistent reflux symptoms underwent wireless pH caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…Foreign body sensation in this study was the most common symptom reported by patients, similar results were showed in some studies based on Bravo pH capsule system [5,19]. Endoscopic removal should be performed when patients have serious symptoms for more than 48 hours [20] or capsule was still attached for more than two weeks.…”
Section: Discussionsupporting
confidence: 85%
“…Foreign body sensation in this study was the most common symptom reported by patients, similar results were showed in some studies based on Bravo pH capsule system [5,19]. Endoscopic removal should be performed when patients have serious symptoms for more than 48 hours [20] or capsule was still attached for more than two weeks.…”
Section: Discussionsupporting
confidence: 85%
“…However this increment of GER had a minimal effect on the overall interpretation of the BRAVO study. The increase in diagnostic yield of GER and symptom correlation by adding the second day has been well demonstrated in adult studies, (22, 23) however the potential effect of anesthesia on the diagnostic yield has not been thoroughly evaluated. We observed that only 1.3% of children with abnormal acid exposure using 6% cut off on the worse day would have been reclassified as being normal if we exclude the 1 st hour of the study and 2% if we exclude the 1 st 2 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The 24-hour pH-metry and, when appropriate, the pHmetry-impedance should be performed, considering that the observation time of 24 hours for the pH-metry might possibly be not enough to characterize acid reflux (8) .…”
Section: Discussionmentioning
confidence: 99%
“…As such, before attributing the reflux to a nonacid component, it should be remembered that these patients may really have acid reflux that was not characterized by the conventional 24-hour pH-metry test. The patient may present normal findings one day and abnormal findings the next day: 25% of the cases monitored by a telemetric capsule ("Bravo" system) that were previously considered normal by conventional 24-hour pH-metry test, when studied for 48 hours showed pathological patterns of acid esophageal reflux (8) . Therefore, the ideal condition would be to test the reflux with the telemetric capsule for 48 hours, which is not possible in an everyday situation.…”
Section: Prolonged Ph-metrymentioning
confidence: 99%